Maqashid sharia: relevance of sharia compliance in modern Islamic banking / Henny Sulastri ... [et al.] - Sulastri, Henny; Anggraeni, Erike; Nurmalia, Gustika; Iqbal, Muhammad (Universiti Teknologi Mara Selangor, 2023)
This study aims to compare the performance of Islamic banking in Indonesia and Malaysia using the Maqashid Sharia Index (MSI). The data were processed quantitatively with a total sample of 18 Islamic commercial banks through purposive sampling in Indonesia and Malaysia. Disclosure of MSI is carried out by analyzing annual banking reports for the period 2016−2021 obtained from the central banks of each country and the website of each bank concerned. They tested the hypothesis using the Independent Sample t-Test with the SPSS application version 26. This study proves that the performance of Islamic banks in Indonesia and Malaysia in 2016−2021 experienced differences in achieving Islamic maqashid educational goals (sig. 0.016 < 0.05). On the other hand, this study proves that there is no difference in the performance of Islamic banks in Indonesia and Malaysia in 2016−2021 in achieving maqashid sharia, the goal of justice (sig. 0.321 > 0.05), the purpose of maslahah (sig. 0.920 > 0.05), and the overall maqashid index (sig. 0.416 > 0.05).